The impact of social participation on Subjective Wellbeing in the older adult: the mediating role of anxiety and the moderating role of education - Qing, Zaihua; Wu, Caihong; Gao, Tao (Frontiers in Public Health, 2024)
The study aims to examine the mediating role of anxiety in the relationship between social participation and Subjective Well-being among Chinese older adults. Additionally, it investigates the moderating effect of education in this relationship. The data came from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) published by Peking University, with a sample size of 10,626 individuals aged 60 years and above. The results found that, 1)The social participation significantly and positively predicted Subjective Well-being; 2)Anxiety partially mediated the effect between social participation and Subjective Well-being. The mediating effect value was 0.103; 3)Education plays a moderating role in the impact of social participation on Subjective Well-being. In summary, social participation can reduce the anxiety and enhance their Subjective Well-being. Meanwhile, the effect of social participation on Subjective Well-being was the greatest for the elderly with high education. The findings suggest that community-led activities can be initiated to improve social participation in the elderly. Furthermore, educational courses could be provided to support the healthy aging of older adults in China.